Deficiência, direitos das pessoas com deficiência e tópica jurídica: o convívio antinômico entre os pontos de vista biomédico e biopsicossocial no direito brasileiro - Oliveira Neto, Vicente Elísio de (2020)
The present work aims at the social inclusion of persons with disabilities through the enforcement of their rights within the national context. The investigation sought to asses whether or not the biopsychosocial definition of disability has been taken into account as a fundamental feature of the inclusive legal program of persons with disabilities, as well as on public-policy shaping, judicial decisions and legal norms. Therefore, the central problem of this work is to verify if the aforementioned biopsychosocial definition is considered by the State as a guiding notion when laws are being made and enforced. The hypothesis is that the antinomic coexistence between biopsychosocial and biomedical definitions of disability in the context of public-policy shaping, judicial decisions, and legal norms stands as an obstacle to the implementation of the program of special protection of persons with disabilities. Throughout the research, particular attention was given to the question of social exclusion of persons with disabilities from different points of view, such question being treated as a problem associated with the emergence of the typical social formation of the Modern Era. Besides that, an account of the fundaments and strategies that made possible the institution of the legal program of special protection of persons with disabilities was carried out, inasmuch as these individuals partake in group which is socially vulnerable, locally and globally. Then, the referred program, which was substantially modified due to the incorporation of clauses of the Convention on the Rights of Persons with Disabilities, was closely analyzed thought constitutional lenses, in a way that its practical and theoretical developments in Brazil were considered. Finally, it was sought to demonstrate, under the perspective of the “topics and law”, the antinomic coexistence of biopsychosocial and biomedical approaches to disability in the development of the activities of production and enforcement of laws in the Brazilian context. As for the methodology, this work recurred to the dialectical method, as proposed by Aristotle, considering that this is the method upon which the main theorical reference of this thesis is based, i.e., Theodor Viehweg’s Topics and Law. In the conclusion, it is highlighted the centrality of the legal delimitation of the meaning of the expression “persons with disabilities” as a structuring starting point of the legal program of special protection of such individuals, which constitute an irreducible condition to the implementation of their rights.